Pulmonary Surfactant Function in Alveoli and Conducting Airways - Goran Enhorning (Canadian Respiratory Journal)
Surface tension plays a very important role in aeration of the neonate's lungs. Pulmonary surfactant, which is inadequate in the premature infant, modifies surface tension during the act of breathing and is necessary for maintenance of alveolar stability. These facts led to the development of the concept that it might be possible to treat the premature infant by supplementing the infant's inadequate surfactant supply. In addition to maintaining alveolar stability, pulmonary surfactant might also be of vital importance for maintenance of small airway patency. Various conditions, most importantly asthma, might be the reason for a surfactant dysfunction to develop. This in turn might cause airway resistance to increase.